Glucuronidase Gene: A Strong Evidence of a Novel Interaction of Glucuronidase-labeled Gluconacetobacter diazotrophicus with Spinach, Spinacia oleracea L. Seedlings - Masyab, Hikmat M.; Al-Nema, Qutaiba S.; Al-Mallah, Mozahim Q. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Gluconacetobacter diazotrophicus lives inside plant tissue cells in the form of colonies and excretes about half of the fixed nitrogen, which offers potential power that improves plant growth. The aim of this study is to find the interaction of glucuronidase (GUS)-labeled G. diazotrophicus with spinach seedlings and the detection of GUS genes using X-gluc dye (5-bromo-4-chloro-3-indolyl-β-D- glucuronic acid). The GUS protocol is used to detect GUS-labeled G. diazotrophicus in spinach seedling tissues by chemical detection using X-gluc dye. The results show that the spinach seedlings are successfully infected with GUS-labeled G. diazotrophicus , with the survival of the seedlings throughout their growth period and an improvement in the growth of pollinated seedlings. The outcomes of the microscopic inspection of the root slices reveal the presence of bacterial cells at the root tips and their concentration in the area of the cell walls of the peripheral cells. Furthermore, the findings of microscopic examinations of longitudinal sections for cotyledons show the presence of a number of bacteria within epidermal cell walls. This indicates that the determinants of the interaction between these bacteria and spinach seedlings are suitable for the expression of the gene responsible for the formation of the nitrogenase enzyme.